Knowledge Management Strategies Supported by ICT for the Improvement of Teaching Practice: A Systematic Review - Miguel-Angel Romero-Ochoa; Julio-Alejandro Romero-González; Alonso Perez-Soltero; Juan Terven; Teresa García-Ramírez; Diana-Margarita Córdova-Esparza; Francisco-Alan Espinoza-Zallas (Information)
In the modern digital ecosystem, the effective management of knowledge and the integration of information and communication technologies are the keys to revolutionizing educational practices within higher education institutions. This study presents a systematic review of recent literature, examining how the incorporation of information and communication technologies facilitates the creation and transfer of knowledge, enables collaboration among educators, and supports continuous professional development. We explore the benefits of personalized learning and the application of technological tools to enhance collaboration, access to educational resources, and pedagogical reflection. The key findings emphasize the role of these tools in promoting teacher interaction and exchange of ideas, highlighting the critical importance of training in digital competency to maximize their impact. The study also identifies challenges, including the need to improve effective knowledge transfer and technological training. In conclusion, effective knowledge management, supported by information and communication technologies, fortifies digital competencies and cultivates a culture of collaboration and content creation in higher education institutions.